Information Technología - Davies, Paul A. (Oxford, New York : Oxford University Press, 2008)
The story information technolgy is a story of machines - from the ancient abacus to the small powerful computer chips of today. Meet woman who wrote computer programs two hundred years ago, a teenage millionaire, a man who began with a peperclip and ended with a house - and the criminals who want your name and your money. Come and discover the world of information technolgy.
La tecnología de información de la historia es una historia de máquinas, desde el antiguo ábaco hasta los pequeños y potentes chips de computadora de hoy en día. Conoce a una mujer que escribió programas de computadora hace doscientos años, un adolescente millonario, un hombre que comenzó con un bolígrafo y terminó con una casa, y los criminales que quieren tu nombre y tu dinero. Ven y descubre el mundo de la tecnología de la información.
CONTENTS 1 THE COMPUTER AGE 2 IN THE BEGINNING 3 THE FIRST COMPUTERS 4 ALAN TURING 5 THE HISTORY OF THE PC AND OTHERS
Keywords: INFORMATION TECHNOLOGY; INTERNET; BILL GATES